Managing service-oriented organizational citizenship behaviors: A review of research literature - Choo, Ling Suan (2015)
For service organizations, service delivery excellence is a necessity.It is also tightly coupled to the favorable attitudes and behaviors of an organization’s customer-contact employees. Described as service oriented organizational citizenship behaviors, service employees who exhibit high levels of these behaviors are willing to go beyond their formal job description. They display loyalty, participation and dedicated service delivery to customers.Drawing from existing studies, this paper defines the concept of service-oriented organizational citizenship behavior, explains why these behaviors are important for service organizations, and discusses the determinants of service-oriented organizational citizenship behaviors